Dispositivo óptico com semiesferas de elastômeros para monitoramento da pressão em ergômetro para cadeirantes - Freitas, Deny Gomes de (2016)
Forces applied to the human body is essential for tissue growth, posture and locomotion. However, in the sitting position, high-pressure levels for long periods can cause serious damage to the skin and underlying tissues, may lead the individual to death due to complications of pressure ulcers. People with disabilities who have not possible, temporary or permanent, to move, adopt a sitting posture with the use of a wheelchair. Wheelchair presenting decrease or loss of sensory functions are more likely to be affected by ulcers do not realize the discomfort of high levels of pressure in the sitting position. Biomechanics Engineering has studied new technologies ergometers and pressure monitoring equipment on the seat of the wheelchair, with different pressure measuring sensors, considering the cost and the setting up of the equipment. Therefore, a new optical device of low cost and simple constitution for pressure monitoring was developed using image processing of the light intensity generated by the deformation of elastomeric hemispheres against a rigid surface transparent illuminated laterally without the use of liquid sensors. For this, it designed and developed an acquisition program, calibration, processing, image analysis and elastic sensor module that is adapted to seat an ergometer for wheelchair users. To understand the device operation and evaluate the design of the new pressure monitoring system was carried out a numerical modeling for finite element, an experimental analysis, an estimate of the pressure by means of analytical model and an experiment designed to assess the effect of support standing on the pressure distribution on the seat at rest and with manual propulsion. By means of the new pressure device on the seat adjustable ergometer it was developed a new pressure monitoring method in ergometer seat for wheelchair users using an optical principle processed image capture of elastomeric hemispheres deformation using applications in LabVIEW environment. The device enabled the acquisition, analysis and monitoring of pressure levels of mapping image on spinal cord injuries seat performing manual propulsion. The results of the experiments with spinal cord injury, demonstrated that the rise foot support increases significantly (p <0.05) and the average maximum pressure in the ischial region. The optical mapping elastomeric hemispheres for monitoring image by pressing the ergometer seat, was an important tool in assessing the ergonomics of the configuration of a wheelchair and postural adjustment with the potential to develop further research in the area of disabled wheelchair users.